Nodular hyperplasia presenting as a mediastinal mass: Three case reports. Issue 34 (August 2018) - Kim, Do Hun; Kim, Dong Wook; Shin, Gi Won; Lee, Yoo Jin; Cho, Young Jun; Park, Ha Kyoung; Ha, Tae Kwun; Park, Ji Sun; Jung, Soo Jin; Ahn, Ki Jung; Moon, Sung Ho
Abstract: Rationale: Based on imaging and biopsy results, surgical removal of mediastinal nodular hyperplasia (MNH) may be unnecessary, and mediastomy may be avoidable. Patient concerns: We report three cases of nodular hyperplasia presenting as a mediastinal mass on imaging studies during a health check-up or for the evaluation of known abscess in the right masticator and submandibular spaces. Interventions: In the first two cases, surgical excision was performed, and in the third case, US-guided core needle biopsy was performed. Diagnoses: Histopathological examination revealed MNH in the first two cases, and histologic examination suggested MNH. Outcomes: In the first two cases, there were no associated complications after successful surgical removal. In the third case, surgery was not performed because of old age and no associated symptoms. Lessons: MNH may mimic mediastinal tumors on imaging studies. Accordingly, awareness of imaging features, interval changes, associated symptoms, and biopsy results may be necessary for the appropriate management of MNH.